Local Production of Fatty Acid–Binding Protein 4 in Epicardial/Perivascular Fat and Macrophages Is Linked to Coronary Atherosclerosis. Issue 5 (May 2016) - Furuhashi, Masato; Fuseya, Takahiro; Murata, Masaki; Hoshina, Kyoko; Ishimura, Shutaro; Mita, Tomohiro; Watanabe, Yuki; Omori, Akina; Matsumoto, Megumi; Sugaya, Takeshi; Oikawa, Tsuyoshi; Nishida, Junichi; et al.
Abstract : Objective—: Fatty acid–binding protein 4 (FABP4) is expressed in adipocytes and macrophages, and elevated circulating FABP4 level is associated with obesity-mediated metabolic phenotype. We systematically investigated roles of FABP4 in the development of coronary artery atherosclerosis. Approach and Results—: First, by immunohistochemical analyses, we found that FABP4 was expressed in macrophages within coronary atherosclerotic plaques and epicardial/perivascular fat in autopsy cases and macrophages within thrombi covering ruptured coronary plaques in thrombectomy samples from patients with acute myocardial infarction. Second, we confirmed that FABP4 was secreted from macrophages and adipocytes cultured in vitro. Third, we investigated the effect of exogenous FABP4 on macrophages and human coronary artery–derived smooth muscle cells and endothelial cells in vitro. Treatment of the cells with recombinant FABP4 significantly increased gene expression of inflammatory markers in a dose-dependent manner. Finally, we measured serum FABP4 level in the aortic root (Ao-FABP4) and coronary sinus (CS-FABP4) of 34 patients with suspected or known coronary artery disease. Coronary stenosis score assessed by the modified Gensini score was weakly correlated with CS-FABP4 but was not correlated with Ao-FABP4. A stronger correlation ( r =0.59, P <0.01) was observed for the relationship between coronary stenosis score and coronary veno-arterial difference in FABP4 level, (CS-Ao)-FABP4, indicating local production of FABP4 during coronary circulation in the heart. Multivariate analysis indicated that (CS-Ao)-FABP4 was an independent predictor of the severity of coronary stenosis after adjustment of conventional risk factors. Conclusions—: FABP4 locally produced by epicardial/perivascular fat and macrophages in vascular plaques contributes to the development of coronary atherosclerosis. Abstract : Supplemental Digital Content is available in the text.